Management of Musculoskeletal Injuries in the Trauma Patient - Smith, Wade R.; Stahel, Philip F. (Springer New York : Imprint: Springer, 2014)
Management of Musculoskeletal Injuries in the Trauma Patient summarizes the most current concepts and clinical practices for the management of the patient with musculoskeletal traumatic injuries. The text covers optimal time frames for stabilization of orthopedic injuries and strategies to mitigate systemic injury while minimizing damage due to pelvic, spine and long bone trauma. The volume covers the gamut of traumatic axial and extremity injuries, including cervico-lumbar-thoracic spine injuries, spinal cord injuries, long bone fractures with special emphasis on the femoral shaft, pelvic and acetabular injuries, open fractures, mangled extremities, upper extremity injuries, combination and severe soft tissues injuries and periarticular fractures.  These are discussed in the context of isolated injury and combined with orthopedic injuries of the brain, abdomen, chest and other musculoskeletal injuries. Written by internationally recognized experts, Management of Musculoskeletal Injuries in the Trauma Patient is a valuable resource for orthopedic surgeons.